PERLINDUNGAN HUKUM TERHADAP ANAK DI BAWAH UMUR DALAM UPAYA MENGEMBANGKAN KUALITAS SUMBER DAYA MANUSIA LEGAL PROTECTION ON CHILDREN UNDER THE AGE QUALITY EFFORTS IN DEVELOPING HUMAN RESOURCES - Abdikoro, HM (Universitas Prof. Dr. Moestopo (Beragama), 2010)
The analysis of the early marriage in regards to the law with the protection of the under age child towards the development of the quality of human resources, that the results of this research was qualified as. the legal research that wasnter and multi disciplinary, so as the source of the data that came from the bibliography research, was supported by results of field work through the interview. The data was gathered to be analyzed through the juridical analysis method quantitative by depicting the data in accordance with the problem henceforth was interpreted, systemized, as well as was given by the argumentation to get the conclusion. Results of the research showed evidently the lower age limit for the woman to be married resulted in the rate of the birth being higher, also showed the existence of the life in the household not harmonious. In the implementation of the marriage, the manipulation of the age, without the courts dispensation happened. Factors that affected it in part, the free association, the culture the tradition, education, economics, as a result the development of human resources was doubted, become more immature, often quarrelling, the high divorce, and often were being sick. The child was forced to drop out of school, the child lost the cheerful life in the childhood, and hindered to psychological development the identity of the child was forced to become fast mature as adult. In connection with that then marriage regulations of the number 1 in 1974 determined the age limit to be married, the man in 19 years old whereas the woman is 16 years old. 1